The late Neoproterozoic Sierra de las Ánimas Magmatic Complex and Playa Hermosa Formation, southern Uruguay, revisited: Paleogeographic implications of new paleomagnetic and precise geochronologic data - Rapalini, Augusto Ernesto (2014)
A new paleomagnetic study was carried out on 15 sites of the Sierra de las Ánimas complex, exposed in SE Uruguay. A paleomagnetic remanence was isolated at six sites, and this direction is likely to be pre-tectonic and primary. Mean directions from five of these sites are consistent with the SA2 paleomagnetic pole, which is based on a previous paleomagnetic study of the complex. A new paleomagnetic pole was computed for compiled results from the Sierra de las Ánimas complex (SAn, 12.2° S, 258.9° E, A95: 14.9°). A geochronological study based on U/Pb (SHRIMP) dating of magmatic zircons was also carried out on three samples of the Sierra de las Animas Complex, yielding a grand mean age of 578 ± 4 Ma. The new SAn paleomagnetic pole anchors the Early Ediacaran segment of the Apparent Polar Wander Path for the Río de la Plata craton. Consistency of the new pole with other Ediacaran poles from the Congo-São Francisco craton suggests a coherent Central Gondwana by this time. These data also support a wide Clymene Ocean between the conjoined Río de la Plata–Congo-São Francisco blocks and Western Gondwana, i.e., Amazonia–West Africa. Additional sampling (sixteen samples) was carried out on the basal levels of the glaciogenic Playa Hermosa Formation, exposed in the same area. These samples retain a paleomagnetic component consistent with the previously reported data, confirming the original pole position. U–Pb (SHRIMP) dating of detrital zircons reveal a bimodal distribution of Paleoproterozoic (around 2.1 Ga) and late Neoproterozoic ages. The youngest zircons are interpreted as pre-dating to penecontemporaneous with deposition and points to a ≤594 Ma age for deposition of the older levels of the Playa Hermosa Formation. A minimum age of deposition is set by the 578 ± 4 Ma age of the Sierra de las Ánimas magmatism. The low inclination of magnetization indicates that low-latitude (13.0° + 9.5°/−5.5°), Gaskiers-aged glacial deposits are preserved atop the Rio de la Plata craton.